Training, Human Resource Development, and Work Motivation as Determinants of Employee Performance in Microfinance Cooperatives - Dedi Bongga; Petrus Peleng Roreng; Corvis L. Rantererung (Management Study Program, Universitas Kristen Indonesia Paulus, 2026)
This study aims to analyze the influence of training programs, human resource development, and work motivation on employee performance at KSP Balo’ Toraja. The research employed a quantitative approach using a survey method. Data were collected through questionnaires distributed to 71 employees selected using a saturated sampling technique. The data were analyzed using multiple linear regression with the assistance of SPSS software. The results indicate that training programs and human resource development have a positive and significant effect on employee performance. Work motivation also shows a positive influence on employee performance, although with a relatively lower contribution compared to other variables. Simultaneously, training, human resource development, and work motivation significantly affect employee performance with a coefficient of determination (R²) of 96.8%, indicating that the model has a strong explanatory power. These findings suggest that improving employee competencies through structured training, sustainable HR development, and motivational support can enhance organizational performance, particularly in microfinance cooperative institutions. This study contributes to the human resource management literature by providing empirical evidence from the Indonesian cooperative sector.